Incidence and Risks of Congenital Anomalies of Kidney and Urinary Tract in Newborns: A Population-Based Case–Control Study in Taiwan. Issue 5 (February 2016) - Tain, You-Lin; Luh, Hsing; Lin, Ching-Yuang; Hsu, Chien-Ning
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Congenital anomalies of the kidney and urinary tract (CAKUT) are 1 of the major factors in young adults needing renal replacement therapy, but there is little extensive assessment of their incidence and risk factors. This study aimed to evaluate trends in the incidence of and risk factors for CAKUT among all births in Taiwan. This population-based case–control study design was conducted using the Taiwan national births registry, which contains detailed information about maternal health and characteristics of newborns, supplied by health professionals. Of 1, 603, 794 newborns registered between 2004 and 2014, 668 infants were reported to have CAKUT. Newborns without congenital anomalies were matched with CAKUT cases by birth year, month, and Apgar score in a ratio of 5:1. Odds ratio (OR) and 95% confidence interval (CI) for developing CAKUT were calculated using a conditional multivariate logistic regression model. The incidence of CAKUT was approximately 4.2 per 10, 000 births. The adjusted ORs for CAKUT in newborns associated with maternal age of 20 to 29 (OR, 2.18; 95% CI, 1.11–4.28), or 30 to 39 (OR, 2.29; 95% CI, 1.17–4.51), maternal gestational diabetes (OR, 2.22, 95% CI, 1.06–4.67), maternal thalassemia/hemochromatosis (OR, 2.67; 95% CI, 1.35–5.27), polyhydramnios or oligohydramnios (OR, 9.16; 95% CI, 5.46–15.37), birth parity >1 (OR, 0.27; 95% CI, 0.15–0.50), having a gestational age <37 weeks (OR, 1.48; 95% CI, 1.23–1.78), and being a boy (OR, 1.83; 95% CI, 1.53–2.19). Infants of mother with gestational diabetes were more likely to have congenital anomalies, small gestational age (<37 weeks) and low birth weight. CAKUT are associated with several maternal health risk factors. As Taiwan has the highest prevalence and incidence rates of end-stage renal disease in the world, these findings strongly support the need to develop professional guidelines for prenatal counseling and management of women at risk of adverse birth outcomes, to prevent kidney disease progression and reduce complications.